Potential biomarkers of IFN-γ, IL-2 and CXCL9 for diagnosis of Q fever disease - Purba, Hastuti Handayani S; Yasmon, Andi (Published by Universitas Gadjah Mada, 2024)
The pathogen responsible for Q fever disease, Coxiella burnetii, is a zoonosis classified as a pathogen due to its airborne transmission. The C. burnetii infection could be both acute or chronic in humans. The main and most common entry of the pathogens to the body is through the breathing of polluted aerosols containing a resistant substance similar to C. burnetii spores. This small cell variant (SCV) or spore-like morphotype is extremely stress-resistant, therefore inadequate treatment causes serious effects even death. Due to the diversity of clinical manifestations of Q fever and the presence of less specific and sensitive diagnoses for other diseases, multiple platforms for exploring Q fever biomarkers are required. Apart from serological studies to determine a biomarker for Q fever, it will be prudent to concentrate on the more appropriate cell-mediated immune response. This article discusses C. burnetii causing Q fever disease and how the host develops humoral and cellular immunity, particularly IFN-γ, IL-2 and CXCL9, as potential biomarkers for the diagnosis of Q fever disease.